Optical and Crystal Structure Properties of ZnO Nanoparticle Synthesized through Biosynthesis Method for Photocatalysis Application - Sri Wahyu Suciyati; Posman Manurung; Junaidi Junaidi; Rudy Situmeang (Universitas Gadjah Mada, 2024)
In this study, zinc oxide nanoparticles (ZnO NPs) were synthesized from zinc nitrate hexahydrate precursor and mango leaf extract (MLE). The purpose of this research was to investigate the crystal structure and optical properties exhibited by ZnO NPs for photocatalytic applications. ZnO NPs produced from various concentrations of sodium hydroxide (NaOH) and the addition of MLE during the synthesis stage demonstrated intriguing physical structure and optical properties. XRD characterization results revealed the attainment of a pure ZnO phase with a high crystallinity degree in all samples. Biosynthesis with MLE unveiled minor peaks corresponding to the cellulose phase. The achieved crystallite size ranged from 15–28 nm. The FTIR patterns detected in the wavenumber range of 600–4000 cm−1 indicated successful crystallization of all ZnO NPs samples. The band gap energy for each sample (ZnO-A to ZnO-E) is indicated to be in the range of 3.25, 3.25, 3.26, 3.31, and 3.17 eV, as demonstrated by the Tauc relation. The effect of MB degradation by the ZnO-E photocatalyst is revealed by the photodegradation of 96.46%.